2019
DOI: 10.14198/jhse.2019.143.03
|View full text |Cite
|
Sign up to set email alerts
|

Weight status, physical activity and self-concept in primary school children

Abstract: Objective: The self-concept, self-esteem and body image of schoolchildren is being compromised due to stigmatization and discrimination in many areas of their lives. Recent studies have shown different associations between those variables and fitness. The objective of this study was to analyse the relationship between weight status, physical activity and self-concept in 103 schoolchildren (63 girls) aged 8-12 years. Design and method: The design was cross-sectional relational. The sampling was non-probabilisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…In adolescents, body dissatisfaction has been found in the range between 12 and 16 years of age without significant differences between sexes (Baile et al, 2002); significant relationships between body appreciation and body mass index, as well as body appreciation and self-esteem (Jauregui & Bolaños, 2011); greater body appreciation but high indices of body pressure by context (Sundgot et al, 2021) and greater body appreciation in those who practice some sport, than in those who do not (Fischetti et al, 2020;Soulliard et al, 2021); similarly, high levels of body appreciation have been found in those adolescents who have high levels of physical activity (Rosa, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In adolescents, body dissatisfaction has been found in the range between 12 and 16 years of age without significant differences between sexes (Baile et al, 2002); significant relationships between body appreciation and body mass index, as well as body appreciation and self-esteem (Jauregui & Bolaños, 2011); greater body appreciation but high indices of body pressure by context (Sundgot et al, 2021) and greater body appreciation in those who practice some sport, than in those who do not (Fischetti et al, 2020;Soulliard et al, 2021); similarly, high levels of body appreciation have been found in those adolescents who have high levels of physical activity (Rosa, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…El tejido muscular esquelético disminuye alrededor de un 40% entre los 20 y los 60 años, sin embargo, a través del ejercicio físico se puede revertir parcialmente la pérdida de masa muscular y consecuentemente los niveles de fuerza (Doherty, 2003). Con el envejecimiento, ocurren cambios en la composición corporal, como aumento de la adiposidad y disminución de la masa corporal magra, en particular la masa muscular esquelética (St-Onge, 2005;Guillamon & Cantó, 2017). Jansen et al (2002), determinaron los puntos de corte para clasificar la sarcopenia mediante la cuantificación de la masa muscular (kg) por BIA corregido para la talla (m2), que establece el Índice de Masa Muscular (IMM).…”
Section: Introductionunclassified
“…En este sentido, la realización de actividad física (en adelante A.F) durante la adolescencia es un indicador clave para establecer prácticas de vida saludable, destacando, por una parte, la disminución de los niveles de sedentarismo e inactividad física en los adolescentes (Kumar, Robinson & Till, 2015;Menéndez & González, 2019), y por otra la estimulación 2021, Retos, 42, 785-797 © Copyright: Federación Española de Asociaciones de Docentes de Educación Física (FEADEF) ISSN: Edición impresa: 1579-1726. Edición Web: 1988-2041 del desarrollo físico, cognitivo y social (Duda & Ntoumanis, 2003;Guillamón, Canto & López, 2019). En los últimos años, las investigaciones sobre la A.F.…”
Section: Introductionunclassified